2001
DOI: 10.1080/02652030110035084
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of heterocyclic aromatic amines in the Swiss diet: analytical method, exposure estimation and risk assessment

Abstract: A total of 86 meat samples, prepared in restaurants or homes, ready to eat (including poultry and fish) and 16 commercial samples such as bouillon (cubes) were analysed for heterocyclic aromatic amines (HAA). The analytical method consisted of an acidic extraction, clean-up on a cation exchange cartridge followed by an analogous HPLC step to recover the following HAA: IQ, MeIQ, MeIQx, 4,8-DiMeIQx, PhIP and 7,8-DiMeIQx. The HAA containing HPLC-fractions were collected, the HAA identified and quantified using tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 46 publications
(73 reference statements)
4
50
1
Order By: Relevance
“…3. Norharman, IQ, Trp-P-1, MeIQ, 4,8-MeIQx and PhIP were positively identified, and its contents (Table 5) were in accordance with those described in the literature [18,20,[33][34][35][36][37].…”
Section: Applicationsupporting
confidence: 82%
“…3. Norharman, IQ, Trp-P-1, MeIQ, 4,8-MeIQx and PhIP were positively identified, and its contents (Table 5) were in accordance with those described in the literature [18,20,[33][34][35][36][37].…”
Section: Applicationsupporting
confidence: 82%
“…It was also not detected in chop and steak samples by Knize et al (1995Knize et al ( , 1998, and in cooked roast and steak with different cooking methods (pan-fried, oven-broiled, and grilled-barbecued) and to a doneness of rare, medium, well done, and very well done by Sinha et al(1998). Rivera, Curto, Pais, Galceran, and Puignou (1996) found 7 ng/g IQ and 8 ng/g MeIQ in grilled beef, while Zimmerli, Rhyn, Zoller, and Schlatter (2001) showed that there was no amount of IQ in grilled pork chop while the content of MeIQ was 1.4 ng/g. In our study, 0.18 ng/g MeIQ was detected in meatball with black pepper fried only at 200 C. However, the reduction of black pepper on the formation of MeIQ in meatball was up to 100%.…”
Section: Treatmentmentioning
confidence: 57%
“…The introduction of DNA array technology in colorectal cancer epidemiology could favor the identification of aspects concerning cancer risk, such as the combinations of HAAs exposure and genetic polymorphisms (Zimmerli, Rhyn, Zoller, & Schlatter, 2001). Another strategy is based in the utilization of the mutagen-sensitivity assay, which reflects both early biological effects of exposure to genotoxic carcinogens and individual cancer susceptibility (Bonassi et al, 2000;El-Zein et al, 2006).…”
Section: New Trends and Strategies On Investigationmentioning
confidence: 98%